Low-Cost and Energy-Efficient Security System Using Passive Infrared Sensor (Ir) (International Journal of Food and Nutritional Sciences, 2021)
This project introduces a passive Infrared sensor "IR" based security system. We can save power and manage effectively using this sensor at a low cost and with a little amount of memory space. The IR sensor detects changes in infrared radiation levels when an intruder or human passes through the system or location where it is installed. Depending on the change in radiation levels, voltages fluctuate, and with this voltage, the signal is amplified, and therefore sound is created. As a result, it is useful in a variety of applications and fields. When compared to the current system, this type of technology has numerous advantages. The term IR sensor refers to a passive infrared sensor. The primary ideology is one of security. This is based on an IR sensor and an IC that generates a siren or buzzer sound. The IR sensor detects the infrared radiation generated by humans and generates a digital result. It is most commonly found in motion detectors, security alarms, and automatic lighting applications. They detect movement by changing the amount of infrared radiation. This digital output is then sent to the Arduino Uno.